Effects of pinealectomy and exogenous melatonin on serum leptin levels in male rat - Canpolat, S; Sandal, S; Yilmaz, B; Yasar, A; Kutlu, S; Baydas, G; Kelestimur, H (Elsevier Science Bv, 2001)
The effects of pinealectomy and exogenous melatonin (N-acetyl-5-methoxytryptamine) on serum leptin levels were investigated in rats. Exogenous administration of melatonin to intact rats resulted in significant decreases in serum leptin levels (P < 0.05) compared to those of the intact control group. Serum leptin levels were significantly elevated in the pinealectomised rats in comparison to the sham-pinealectomised animals (P < 0.001) and were significantly suppressed by exogenous administration of melatonin compared to those of non-treated pinealectomised rats ( P < 0.001). Hormone concentrations in the melatonin-treated pinealectomised group were found to be similar to those seen in the sham-pinealectomised group. These results suggest that pineal gland has an effect on leptin release. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: leptin; melatonin; pinealectomy; (rat)